Green Tea Extract Enhances the Oxidative Stability of DHA-Rich Oil - Caroline Waingeh Nain; Gwennaëlle Berdal; Phan Thi Phuong Thao; Eric Mignolet; Marine Buchet; Melissa Page; Yvan Larondelle (Antioxidants, 2021)
Docosahexaenoic acid (DHA) is one of the most important omega-3 polyunsaturated fatty acids, with proven health-promoting properties. However, oils with a very high content in DHA (DHAO) are extremely susceptible to oxidation, which affects shelf stability and limits incorporation in food products. Green tea extracts (GTE) are potential candidates for the protection of these oils, but their use in such oils has not been previously reported. This study investigated the effect of GTE (160 ppm, 400 ppm, 1000 ppm) and α-tocopherol (80 ppm, 200 ppm, 500 ppm) on the oxidative stability of a DHAO over a 9-week storage at 30 °C. The oxidative status was monitored during storage by the measurement of peroxide value (PV) and p-anisidine value (p-AV). Changes in eicosapentaenoic acid (EPA) and DHA content, as well as in catechins and tocopherol contents, were also evaluated. The addition of GTE enhanced the oxidative stability of DHAO by reducing the formation of peroxides and secondary oxidation products, whereas α-tocopherol had no significant effect on the PV of oil during storage but led to a significantly higher p-AV. The EPA and DHA content of DHAO was stable in GTE-supplemented samples whereas a decrease was observed in the control and α-tocopherol-supplemented samples. GTE also delayed the degradation of tocopherols initially present in the oil, while catechins resulting from the addition of GTE decreased progressively during the storage period.